Associations of inter-annual rainfall decreases with subsequent HIV outcomes for persons with HIV on antiretroviral therapy in Southern Africa: a collaborative analysis of cohort studies - Trickey, A.; Bosomprah, S.; Chirimuta, L.; et al. (BMC Infectious Diseases, 2023)
Background Periods of droughts can lead to decreased food security, and altered behaviours, potentially afecting outcomes on antiretroviral therapy (ART) among persons with HIV (PWH). We investigated whether decreased rainfall is associated with adverse outcomes among PWH on ART in Southern Africa. Methods Data were combined from 11 clinical cohorts of PWH in Lesotho, Malawi, Mozambique, South Africa, Zambia, and Zimbabwe, participating in the International epidemiology Databases to Evaluate AIDS Southern Africa (IeDEA-SA) collaboration. Adult PWH who had started ART prior to 01/06/2016 and were in follow-up in the year prior to 01/06/2016 were included. Two-year rainfall from June 2014 to May 2016 at the location of each HIV centre was summed and ranked against historical 2-year rainfall amounts (1981–2016) to give an empirical relative percentile rainfall estimate. The IeDEA-SA and rainfall data were combined using each HIV centre’s latitude/longitude. In individ ual-level analyses, multivariable Cox or generalized estimating equation regression models (GEEs) assessed associa tions between decreased rainfall versus historical levels and four separate outcomes (mortality, CD4 counts<200 cells/mm3 , viral loads>400 copies/mL, and>12-month gaps in follow-up) in the two years following the rainfall period. GEEs were used to investigate the association between relative rainfall and monthly numbers of unique visi tors per HIV centre. Results Among 270,708 PWH across 386 HIV centres (67% female, median age 39 [IQR: 32–46]), lower rainfall than usual was associated with higher mortality (adjusted Hazard Ratio: 1.18 [95%CI: 1.07–1.32] per 10 percen tile rainfall rank decrease) and unsuppressed viral loads (adjusted Odds Ratio: 1.05 [1.01–1.09]). Levels of rainfall were not strongly associated with CD4 counts<200 cell/mm3 or>12-month gaps in care. HIV centres in areasBackground Periods of droughts can lead to decreased food security, and altered behaviours, potentially afecting outcomes on antiretroviral therapy (ART) among persons with HIV (PWH). We investigated whether decreased rainfall is associated with adverse outcomes among PWH on ART in Southern Africa. Methods Data were combined from 11 clinical cohorts of PWH in Lesotho, Malawi, Mozambique, South Africa, Zambia, and Zimbabwe, participating in the International epidemiology Databases to Evaluate AIDS Southern Africa (IeDEA-SA) collaboration. Adult PWH who had started ART prior to 01/06/2016 and were in follow-up in the year prior to 01/06/2016 were included. Two-year rainfall from June 2014 to May 2016 at the location of each HIV centre was summed and ranked against historical 2-year rainfall amounts (1981–2016) to give an empirical relative percentile rainfall estimate. The IeDEA-SA and rainfall data were combined using each HIV centre’s latitude/longitude. In individ ual-level analyses, multivariable Cox or generalized estimating equation regression models (GEEs) assessed associa tions between decreased rainfall versus historical levels and four separate outcomes (mortality, CD4 counts<200 cells/mm3 , viral loads>400 copies/mL, and>12-month gaps in follow-up) in the two years following the rainfall period. GEEs were used to investigate the association between relative rainfall and monthly numbers of unique visi tors per HIV centre. Results Among 270,708 PWH across 386 HIV centres (67% female, median age 39 [IQR: 32–46]), lower rainfall than usual was associated with higher mortality (adjusted Hazard Ratio: 1.18 [95%CI: 1.07–1.32] per 10 percen tile rainfall rank decrease) and unsuppressed viral loads (adjusted Odds Ratio: 1.05 [1.01–1.09]). Levels of rainfall were not strongly associated with CD4 counts<200 cell/mm3 or>12-month gaps in care. HIV centres in areas with less rainfall than usual had lower numbers of PWH visiting them (adjusted Rate Ratio: 0.80 [0.66–0.98] per 10 percentile rainfall rank decrease). Conclusions Decreased rainfall could negatively impact on HIV treatment behaviours and outcomes. Further research is needed to explore the reasons for these efects. Interventions to mitigate the health impact of severe weather events are required.
Research Article